2020
DOI: 10.3390/f11030299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wood Moisture Content and the Level of Acetylation on Brown Rot Decay

Abstract: Acetylation is one of the most common types of wood modification and is commercially available throughout the world. Many studies have shown that acetylated wood is decay resistant at high levels of acetylation. Despite its widespread use, the mechanism by which acetylation prevents decay is still not fully understood. It is well known that at a given water activity, acetylation reduces the equilibrium moisture content of the wood cell wall. Furthermore, linear relationships have been found between the acetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
5
11
0
Order By: Relevance
“…∆MC should represent the extra amount of moisture generated by the fungus. Consistent with Zelinka, Kirker, Bishell, and Glass [38], our results showed that higher amounts of fungal metabolism, which are reflected in higher mass loss, are associated with higher final moisture content (especially true for T. versicolor and G. trabeum isolates). The reason for the negative value of ∆MC for EM in samples of A. platanoides is not clear, but other authors have also reported this phenomenon [38,39].…”
Section: Moisture Contentsupporting
confidence: 90%
See 3 more Smart Citations
“…∆MC should represent the extra amount of moisture generated by the fungus. Consistent with Zelinka, Kirker, Bishell, and Glass [38], our results showed that higher amounts of fungal metabolism, which are reflected in higher mass loss, are associated with higher final moisture content (especially true for T. versicolor and G. trabeum isolates). The reason for the negative value of ∆MC for EM in samples of A. platanoides is not clear, but other authors have also reported this phenomenon [38,39].…”
Section: Moisture Contentsupporting
confidence: 90%
“…The calculated mass loss correlated well with the calculated moisture content of the wood samples. A positive linear trend can be observed for the relationship between mass loss and moisture content, as already described in the literature [35,38].…”
Section: Moisture Contentsupporting
confidence: 82%
See 2 more Smart Citations
“…Wood after acetylation 2 of 13 shows lower wettability, equilibrium moisture content [15,16], and water uptake [13]. In addition, dimensional stability [17][18][19] and resistance to decay [12,20,21] are prominently improved. As a result of these advantageous properties, acetylation has been developed to the industrial scale and commercialized [22].…”
Section: Introductionmentioning
confidence: 99%